Workplace culture of health and employee physical activity: the moderating effects of gender and depression - Michele W. Marenus; Mary Marzec; Amy Kilbourne; Natalie Colabianchi; Weiyun Chen (Discover Psychology, 2024)
Abstract Introduction Promoting physical activity (PA) at work effectively decreases the risk of chronic disease and increases productivity. Despite the well-established benefits of PA, only 24% of adults meet the PA Guidelines for Americans. Advancing a culture of health (COH) may improve employees’ physical activity levels. The purpose of this study was to determine the effects of workplace culture of health, gender, and depression on employee physical activity. Methods Employees (n = 12,907) across 14 companies voluntarily completed the Workplace Culture of Health (COH) Scale, the Patient Health Questionnaire (PHQ-2), and questions on PA engagement. A logistic regression was performed to determine the effects of workplace COH, gender, and depression risk on the likelihood of engaging in 150 min of moderate to vigorous PA and in strength training 2 × per week. Results Workplace COH scores were associated with increased odds of PA engagement (OR = 1.058, p < 0.001). Further, gender and depression risk moderated the relationship between workplace COH and PA engagement (OR = 0.80, p = 0.026). For employees at risk for depression, an increase in COH scores was associated with higher PA for men, but not women. For employees not at risk for depression, an increase in COH scores was associated with higher PA for males and females. Conclusion Establishing a health-supportive workplace culture may increase PA, which is essential to improving population health. The differential findings by gender and depression risk illustrate the complexity of PA engagement.